Soluble Interleukin-2 Receptor Predicts Treatment Outcome in Patients With Autoimmune Tubulointerstitial Nephritis. A Preliminary Study - Shiratori-Aso, Satoka; Nakazawa, Daigo; Nishio, Saori; Ueda, Yusho; Eguchi, Mina; Yokoyama, Ai; Yoshikawa, Junpei; Kudo, Takashi; Watanabe-Kusunoki, Kanako; Takeda-Otera, Sayo; Yamamoto, Junya; Matsuoka, Naoko; et al. (Frontiers in Medicine, 2022)
Background: Autoimmune tubulointerstitial nephritis (TIN) is characterized by immune-mediated tubular injury and requires immunosuppressive therapy. However, diagnosing TIN and assessing therapeutic response are challenging for clinicians due to the lack of useful biomarkers. Pathologically, CD4+ T cells infiltrate to renal tubulointerstitium, and soluble interleukin-2 receptor (sIL-2R) has been widely known as a serological marker of activated T cell. Here, we explored the usefulness of serum sIL-2R to predict the treatment outcome in patients with autoimmune TIN. Methods: Study Design: Single-center retrospective observational study. Participants: 62 patients were diagnosed of TIN from 2005 to April 2018 at Hokkaido University Hospital. Among them, 30 patients were diagnosed with autoimmune TIN and treated with corticosteroids. We analyzed the association between baseline characteristics including sIL-2R and the change of estimated glomerular filtration rate (eGFR) after initiation of corticosteroids. Results: The serum sIL-2R level in patients with autoimmune TIN was significantly higher than that in chronic kidney disease patients with other causes. Mean eGFR in autoimmune TIN patients treated with corticosteroids increased from 43.3±20.4 mL/min/1.73 m2 (baseline) to 50.7±19.9 mL/min/1.73 m2 (3 months) (ΔeGFR; 22.8±26.0%). Multivariate analysis revealed that higher sIL-2R (per 100 U/mL, β = 1.102, P < 0.001) level was independently associated with the renal recovery. In ROC analysis, sIL-2R had the best area under the curve value (0.805) and the cutoff point was 1182 U/mL (sensitivity = 0.90, 1-specificity = 0.45). Conclusions: Our study showed that elevated serum sIL-2R levels might become a potential predictive marker for therapeutic response in autoimmune TIN.